Myocardin-Related Transcription Factor A Activation by Competition with WH2 Domain Proteins for Actin Binding - Weissbach, Julia (Mol Cell Biol, 2016)
The myocardin-related transcription factors (MRTFs) are coactivators of serum response factor (SRF)-mediated gene expression. Activation of MRTF-A occurs in response to alterations in actin dynamics and critically requires the dissociation of repressive G-actin–MRTF-A complexes. However, the mechanism leading to the release of MRTF-A remains unclear. Here we show that WH2 domains compete directly with MRTF-A for actin binding. Actin nucleation-promoting factors, such as N-WASP and WAVE2, as well as isolated WH2 domains, including those of Spire2 and Cobl, activate MRTF-A independently of changes in actin dynamics. Simultaneous inhibition of Arp2-Arp3 or mutation of the CA region only partially reduces MRTF-A activation by N-WASP and WAVE2. Recombinant WH2 domains and the RPEL domain of MRTF-A bind mutually exclusively to cellular and purified G-actin in vitro. The competition by different WH2 domains correlates with MRTF-SRF activation. Following serum stimulation, nonpolymerizable actin dissociates from MRTF-A, and de novo formation of the G-actin–RPEL complex is impaired by a transferable factor. Our work demonstrates that WH2 domains activate MRTF-A and contribute to target gene regulation by a competitive mechanism, independently of their role in actin filament formation.